Ground-based microwave radiometry and remote sensing : methods and applications - Karmakar, Pranab Kumar (CRC Press, 2014)
"Ground-based radiometers are currently operated in research labs around the globe and are also used as routine measurement tools for water vapor and temperature profiling. This reference provides a comprehensive picture of ground-based radiometry, starting with the basic principles. It provides information on ground-based instrumentation, retrieval techniques, and temperature structure. The book also covers temperature profiling and water vapor radiometry as well as ozone radiometry and nitrous oxide measurements. In addition, it supplies retrieval algorithms using MATLAB, worked examples of derived products, and polar atmosphere cases. "-- Provided by publisher.
Keywords: Atmospherics.; Atmosphere -- Research.; Radio meteorology.; Radiation -- Measurement.; Microwave measurements.; elektronické knihy; electronic books